THE IMPACT OF FLOODING ON THE OPERATIONAL RELIABILITY OF REAL ESTATE IN THE KURSK REGION - Khaustov, Vladimir (Journal of Applied Engineering Science, 2019)
The example of industrial and residential areas shows the negative impact of the processes of flooding of territories, on the operational reliability of real estate objects. The causes of the manifestation and development of these complex processes are revealed. To overcome the anthropogenic impact on groundwater, technological recommendations have been proposed, economic and social nature.